Computing Skin Cutaneous Melanoma Outcome From the HLA-Alleles and Clinical Characteristics - Dhall, Anjali; Patiyal, Sumeet; Kaur, Harpreet; Bhalla, Sherry; Arora, Chakit; Raghava, Gajendra P. S. (Frontiers in Genetics, 2020)
Human Leukocyte Antigen (HLA) are essential components of the immune system that stimulate immune cells to provide protection and defense against cancer. More than thousands of HLA alleles have been reported in the literature, but only a specific set of HLA alleles are present in an individual. The capability to recognize the cancer-associated mutations by the immune system depends on the presence of a particular set of alleles, that elicit an immune response to fight against cancer. Therefore, the occurrence of specific HLA alleles affects the survival outcome of cancer patients. In the current study, prediction models have been developed using 401 cutaneous melanoma patients for predicting the overall survival (OS) of patients using their clinical data and HLA alleles. We observed that the presence of certain favorable superalleles like HLA-B*55 (HR=0.15, 95% CI 0.034 to 0.67), HLA-A*01 (HR=0.5, 95% CI 0.3 to 0.8), is responsible for the improved OS. In contrast, the presence of certain unfavorable superalleles such as HLA-B*50 (HR=2.76, 95% CI 1.284 to 5.941), HLA-DRB1*12 (HR=3.44, 95% CI 1.64 to 7.2) is responsible for the poor survival. We developed prediction models using key 14 HLA superalleles, demographic, and clinical characteristics for predicting high-risk cutaneous melanoma patients and achieved HR=4.52 (95% CI 3.088-6.609, p-value = 8.01E-15). Eventually, we also provide a web-based service to the community for predicting the risk status in cutaneous melanoma patients (https://webs.iiitd.edu.in/raghava/skcmhrp/).